Emotion Recognition as a Real Strength in Williams Syndrome: Evidence From a Dynamic Non-verbal Task - Laure Ibernon; Claire Touchet; Régis Pochon (Frontiers in Psychology, 2018)
The hypersocial profile characterizing individuals with Williams syndrome (WS), and particularly their attraction to human faces and their desire to form relationships with other people, could favor the development of their emotion recognition capacities. This study seeks to better understand the development of emotion recognition capacities in WS. The ability to recognize six emotions was assessed in 15 participants with WS. Their performance was compared to that of 15 participants with Down syndrome (DS) and 15 typically developing (TD) children of the same non-verbal developmental age, as assessed with Raven’s Colored Progressive Matrices (RCPM; Raven et al., 1998). The analysis of the three groups’ results revealed that the participants with WS performed better than the participants with DS and also than the TD children. Individuals with WS performed at a similar level to TD participants in terms of recognizing different types of emotions. The study of development trajectories confirmed that the participants with WS presented the same development profile as the TD participants. These results seem to indicate that the recognition of emotional facial expressions constitutes a real strength in people with WS.